1994
DOI: 10.1021/bi00201a027
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Studies on Catechol 2,3-Dioxygenase from Pseudomonas putida MT2

Abstract: X-ray absorption spectroscopy has been utilized to investigate the structure of the active site of iron(II) catechol 2,3-dioxygenase from Pseudomonas putida mt2 both in the native and the 2-chlorophenol inhibited forms. XANES (X-ray absorption near edge structure) and EXAFS (extended X-ray absorption fine structure) results allow us to discuss the coordination number and geometry of the ferrous ion in the native enzyme. The metal geometry is not significantly affected by the binding of the inhibitor. The EXAFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…The four residues that we have identified as ligating the active site metal in both FeARD' and NiARD isoforms, His 96, His 98, Asp 102 and His 140, are all strictly conserved across the ARD superfamily (31), and were initially identified as potential ligands via sequence alignment and spatial localization from paramagnetic broadening patterns in NMR data and homology modeling (12). The recently-published crystal structure of MmARD supports the assignment of these residues as the protein-based ligands (17).…”
Section: Discussionmentioning
confidence: 93%
“…The four residues that we have identified as ligating the active site metal in both FeARD' and NiARD isoforms, His 96, His 98, Asp 102 and His 140, are all strictly conserved across the ARD superfamily (31), and were initially identified as potential ligands via sequence alignment and spatial localization from paramagnetic broadening patterns in NMR data and homology modeling (12). The recently-published crystal structure of MmARD supports the assignment of these residues as the protein-based ligands (17).…”
Section: Discussionmentioning
confidence: 93%
“…The higher 1s → 3d peak area at pH 8.5 could be due to higher distortion of the octahedral site as a result of one shorter Fe-N/O bond. Typical 1s → 3d peak areas for octahedral geometries are 3 – 7 × 10 −2 eV,(49) whereas lowering symmetry to a five-coordinate geometry is associated with peak areas of 8 – 13 × 10 −2 eV (2, 3). The measured peak area for the high pH sample is at the high end of what is typically observed for six-coordinate Fe(II), but could reflect a six-coordinate site with deviations from ideal octahedral symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…This region contains one histidine residue, two aspartate residues, and one glutamate residue. For the catechol 2,3-DO from P. putida mt-2, it has been recently suggested that histidine and carboxylate groups from aspartate and/or glutamate residues are responsible for iron(II) coordination (8). It therefore seems reasonable that this region is in the three proteins involved in the coordination of the ferrous iron.…”
Section: Discussionmentioning
confidence: 99%